2009
DOI: 10.2118/09-09-26
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Commercial Bitumen Recovery from the Grosmont Carbonate, Alberta

Abstract: The last few years have seen the end of the Athabasca land play and the revival of interest in Alberta's bitumen resources in carbonate reservoirs. Of these, the Grosmont Formation is the most promising in terms of resource size and concentration. It is also the best known, in terms of having been the subject of several in situ pilots operated in the late '70s and early '80s. The data recorded from these early pilots is priceless in terms of having a touchstone of reality for new process conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…The results from a cold solvent soak test for an 80 cm long full diameter Grosmont core have been previously reported [2]. The core sample was taken from a well located in the LaricinaOsum JV land.…”
Section: Laboratory Testmentioning
confidence: 99%
“…The results from a cold solvent soak test for an 80 cm long full diameter Grosmont core have been previously reported [2]. The core sample was taken from a well located in the LaricinaOsum JV land.…”
Section: Laboratory Testmentioning
confidence: 99%
“…It was concluded that SAGD is not suitable due to low matrix permeability and low fracture porosity. Edmunds et al (2009) analyzed core samples and past CSS pilots in Grosmont, Alberta and concluded the possibility of applying SAGD because of high bulk permeability, being in the order of higher than 10D. The reservoir rock texture includes centimeter-scaled karst and fractures, extensively.…”
Section: Thermal Processes In Fractured Reservoirsmentioning
confidence: 99%
“…The C-D marl (i.e. marl separating the C and D units) occurs at 346 m (Edmunds et al, 2009). The most prolific hydrocarbon reservoirs (based on porosity and thickness) are the C and D units, which contain 80% of total Grosmont bitumen in-place.…”
Section: Geology and Diagenesismentioning
confidence: 99%